2005
DOI: 10.1111/j.1572-0241.2005.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Senna Compared with Conventional PEG-ES Lavage as Bowel Preparation for Elective Colonoscopy: A Prospective, Randomized, Investigator-Blinded Trial

Abstract: An oral high dose of senna is a valid alternative to standard PEG-ES for outpatient colonoscopy preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 25 publications
2
56
1
2
Order By: Relevance
“…The sennosides are generally used in combination with PEG. The use of sennosides without PEG combination is controversial (3). Enema is an agent that evacuates the distal colon and was a basic component of colonoscopy preparation before the introduction of PEG (2).…”
Section: Introductionmentioning
confidence: 99%
“…The sennosides are generally used in combination with PEG. The use of sennosides without PEG combination is controversial (3). Enema is an agent that evacuates the distal colon and was a basic component of colonoscopy preparation before the introduction of PEG (2).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Valverde et al and Chilton et al showed that senna either alone or in combination was associated with more effective colonic cleanliness than other regimens [20,21]. Radaelli et al concluded that high-dose (288 mg) senna was an effective alternative to a standard 4-liter PEG solution, with overall cleansing reported as excellent or good in 90.6% of the senna group and in 79.7% of the PEG group (p = 0.003) [18]. Moreover, Yenidogan et al claimed that administration of senna on the colonoscopy day was effective as a bowel preparation protocol, since only 9.3% of the patients were asked to repeat the examination [4].…”
Section: Discussionmentioning
confidence: 99%
“…The cecal intubation, withdrawal and total colonoscopy time, endoscopic diagnosis, and additional therapeutic procedures (including polypectomy) were recorded. At the end of the colonoscopy, the difficulty of the procedure was rated by the endoscopist using the scale (1 = easy, 2 = fairly easy, 3 = difficult, and 4 = failure to complete the procedure) which was previously used by Radaelli et al [18]. The quality of the colon cleansing was evaluated using the validated Ottawa Bowel Preparation Quality Scale (Table 1) [19].…”
Section: Colonoscopy Procedures and Data Collectionmentioning
confidence: 99%
“…PEG kullan›m› ile barsak temizli¤inde elde edilen baflar›, Radelli ve arkadafllar› taraf›ndan desteklenmemekte, yüksek doz sennosidin PEG'e alternatif olabilece¤i ileri sürülmektedir. 34 Alt G‹S endoskopisinde kolon temizli¤inin iyi olmas› ifllemin baflar›s›nda büyük rol oynasa da tek bafl›na yeterli de¤ildir. ‹fllemi yapan hekimin deneyim ve sabr›, hastan›n uyumu, altta yatan hastal›k baflar›da önemlidir.…”
Section: Tart›flmaunclassified